Numerical investigation into a liquid displacing a gas in thin porous layers. Issue 1 (25th October 2016) - Neumann, Tim; Boettcher, Konrad; Ehrhard, Peter
Abstract: To examine the filling process in a lithium‐ion battery, a numerical model to characterize the displacing flow of a liquid in air‐filled pores of thin heterogeneous porous materials is elaborated. The investigation is based on the volume‐averaged Navier‐Stokes equations for small Reynolds numbers, using a volume‐of‐fluid method to cover the multiphase flow. The flow is investigated with respect to the wall effect and to capillary action within the porous matrix. On the one hand, model experiments with similar particle‐size distributions as in the battery layers are conducted to extract the porosity as function of the wall distance. On the other hand, experiments with the three different porous layers of the battery are performed to receive mean values for the most important properties related to the two‐phase flow. Results for the displacement flow in parts of the battery are presented and discussed, showing a considerable influence of the modeled effects onto the flow characteristics. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)